An Analysis of Question Papers in Different School Subjects at Class X Level - Chandrasekhar, K. (JOURNAL OF INDIAN EDUCATION, 2016)
Examinations play an important role in the Indian system of education. They are so important that they direct the entire teaching-learning process in schools. Examinations use mainly one tool to evaluate the achievement of students and that is the ‘question paper’. So, if public examinations have to stay till a viable mechanism of evaluation comes into effect, question papers used by the State Boards of Education in their public examinations need to be continuously examined and improved, especially for the purpose of improving the quality of education at the school stage. It was in this backdrop that a minor research project to analyse Class X question papers of the Uttar Pradesh the State Board of High School and Intermediate Education was undertaken. The objective of the study is to find out whether the question papers are valid and reliable and what are their strengths and weaknesses.